The World Conference against Racism: Through a Wider Lens - McDougall, Gay (Tufts Archival Research Center, 2005)
Volume 26, Issue 2. Summer/Fall The World Conference against Racism (WCAR) last September broke new ground in confronting racism worldwide, writes the Executive Director of the International Human Rights Law Group. In response to a piece by U.S. Congressman Tom Lantos in the previous issue of The Fletcher Forum, McDougall argues that there was much more to the WCAR than Congressman Lantos noted.